2019
DOI: 10.3389/fimmu.2019.01812
|View full text |Cite
|
Sign up to set email alerts
|

On the Way to Become a Natural Killer Cell

Abstract: Natural Killer (NK) cells are innate lymphocytes playing pivotal roles in host defense and immune-surveillance. The homeostatic modulation of germ-line encoded/non-rearranged activating and inhibitory NK cell receptors (NKRs) determines the capability of these innate lymphocytes to either spare “self” cells or to kill viral-infected, tumor-transformed and heterologous cell targets. However, despite being discovered more than 40 years ago, several aspects of NK cell biology remain unknown or are still being deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
100
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 218 publications
2
100
0
1
Order By: Relevance
“…These CLPs further differentiate into NK cell progenitors (NKP) that are classified into three sequential stages of maturation, named NK cell progenitors (stage 1), pre-NK cells (stage 2), and immature NK cells (stage 3). The early stages of NK cell development and differentiation have been characterized in the context of the bone marrow niche, but pre-NK cells can be detected in the circulation, and other data have shown that they are enriched in extramedullary tissues where subpopulations of mature NK cells reside, suggesting that they have developed locally [3,25,31]. It is known that some NKPs are selectively enriched in SLT, such as lymph nodes and tonsils, as well as in the gastrointestinal tract, liver, and uterus [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These CLPs further differentiate into NK cell progenitors (NKP) that are classified into three sequential stages of maturation, named NK cell progenitors (stage 1), pre-NK cells (stage 2), and immature NK cells (stage 3). The early stages of NK cell development and differentiation have been characterized in the context of the bone marrow niche, but pre-NK cells can be detected in the circulation, and other data have shown that they are enriched in extramedullary tissues where subpopulations of mature NK cells reside, suggesting that they have developed locally [3,25,31]. It is known that some NKPs are selectively enriched in SLT, such as lymph nodes and tonsils, as well as in the gastrointestinal tract, liver, and uterus [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that some NKPs are selectively enriched in SLT, such as lymph nodes and tonsils, as well as in the gastrointestinal tract, liver, and uterus [32][33][34][35][36][37]. The most accepted model of NK cell development occurs in the linear fashion just described above, in which the expression of CD94 marks the commitment to the CD56 bright stage (stage 4), that next differentiate into CD56 dim NK cells (stages 5 and 6) [25,31]. The differentiation into adaptive (also called memory) CD56 dim NK cells could subsequently occur after viral infection, as, for example, the human cytomegalovirus [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations